2016
DOI: 10.3892/ol.2016.5358
|View full text |Cite
|
Sign up to set email alerts
|

A circulating tumor cell cluster-based model for tumor metastasis (Hypothesis)

Abstract: Abstract. Metastasis is the major cause of mortality in patients with malignancies; however, the mechanisms of tumor cell dissemination and metastasis formation are obscure. Circulating tumor cells (CTCs) are believed to be a critical step for distant metastasis and are associated with a poor patient prognosis. The precise processes of metastasis formation from CTCs are vague. In the present study, we hypothesize that two CTC cluster-based mechanisms of tumor cell inoculation in ectopic organs may be viable: i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The most current CTC capture methods with antibodies detecting CTC surface proteins might be less efficient for CTC clusters as compared to single CTCs, possibly because antigens are largely masked by the CTC cluster nature itself. Thus, the real quantification of CTC clusters might be currently underestimated [9]. However, we will explore recent literature on CTC clusters and realize that their implication in cancer aggressiveness should not be neglected, as well as that they may even represent a valuable access to therapeutic optic.…”
Section: Introductionmentioning
confidence: 99%
“…The most current CTC capture methods with antibodies detecting CTC surface proteins might be less efficient for CTC clusters as compared to single CTCs, possibly because antigens are largely masked by the CTC cluster nature itself. Thus, the real quantification of CTC clusters might be currently underestimated [9]. However, we will explore recent literature on CTC clusters and realize that their implication in cancer aggressiveness should not be neglected, as well as that they may even represent a valuable access to therapeutic optic.…”
Section: Introductionmentioning
confidence: 99%
“…The process of malignant tumor metastasis is very complex. It has been confirmed that the invasion of peripheral blood circulation by tumor cells is one of the main ways of distant metastasis dissemination ( 7 ). Circulating tumor cells (CTCs) are tumor cells found in the peripheral blood circulation, their shedding from the primary solid malignancy can be spontaneous or caused by medical treatment ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with CTCs, CTMs effectively reflected the severity of illness and dismal prognosis of patients in our study. Although CTCs have been found in many studies, only a few successful detections of CTC clusters have been reported, especially in PDAC patients (29). We believe that the role of CTMs in current clinical applications and research is largely underestimated.…”
Section: Univariate Analysis ---------------------------------------mentioning
confidence: 93%